Tasks of State Regulation at the Agricultural Sector of Ukraine’s Economy - Halanets, Volodymyr (Theory and Practice of Public Administration, 2019)
The peculiarities of state regulation of the agrarian sphere of the economy are considered. The results of the scientific researches allow to establish that the issues of a comprehensive study of the problem of state regulation of the agrarian sector of the economy remain insufficiently highlighted. The analysis of economic development of Ukraine during 2002-2017 was carried out. The dynamics of GDP of Ukraine at this time, efficiency of production in agriculture are investigated. It is established that the potential of agricultural co-operation in Ukraine is not realized. Due to the large combination of objective and subjective reasons and circumstances, the potential of agrarian reforms in socio-political and socio-economic terms is slowly evolving. The necessity of determining the main tasks of state regulation in the agrarian sector is substantiated. The priority directions of state support for the development of the agricultural sector have been formed. The main tasks of the state regulation of the agrarian sphere of the Ukrainian economy should be: improvement of the state agricultural policy, institutional environment, organizational and economic mechanism, financial and information support, and state support of farmers. It is necessary to ensure the GDP growth of the country, stimulate the creation of new farms and increase their competitiveness. The state should stimulate the development of livestock, viticulture, horticulture and hop farming in farms. To ensure this, it is necessary to give them priority rights to receive plots for horticulture, viticulture, hops and organic farming. The state should promote the development of agricultural cooperation, provide financial support. Such measures will allow to solve a number of important problems - will ensure the reduction of unemployment in Ukraine, the development of a socially oriented economy and а country as a whole.